Inspire and ignite: Enabling factors for early tourism development in Sabah, Malaysia - Marcela Pimid; Azizan Marzuki; Stephen Sampil (Planning Malaysia, 2024)
Community-based tourism (CBT) is renowned worldwide as a sustainable economic development and a means of improving rural communities' welfare and standard of living. Successful CBT greatly depends on local communities’ readiness and active participation in ensuring equal distribution of CBT benefits. This study investigates the readiness of rural communities to engage in CBT under the management of Moyog Agrotourism and Tourism Park (MANTAP), a locally empowered organisation. The theoretical concept is framed by social exchange theory and the tourism development model is adjusted to match the local context. The study employs a cross-sectional approach, examining native perspectives on the early stages of CBT development in upper Moyog areas. Using the qualitative method, the findings reveal substantial local support for the CBT development. The study underscores the importance of demonstrating tourism benefits early on, as well as strong leadership and project legitimacy, which foster credibility and access to tourism resources. Native people who can picture themselves gaining benefits and be part of the tourism planning show more apparent support for tourism development in rural Penampang areas.